Simplified Space Vector Pulse Width Modulation based on Switching Schemes with Reduced Switching Frequency and Harmonics for Five Level Cascaded H-Bridge Inverter - B. Sirisha; P. Satishkumar (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This paper presents a simplified control strategy of spacevector pulse width modulation technique with a three segment switching sequence and seven segment switching sequence for high power applications of multilevel inverters. In the proposed method, the inverter switching sequences are optimized for minimization of device switching frequency and improvement of harmonic spectrum by using the three most desired switching states and one suitable redundant state for each space vector. The proposed three-segment sequence is compared with conventional seven-segment sequence for five level Cascaded H-Bridge inverter with various values of switching frequencies including very low frequency. The output spectrum of the proposed sequence design shows the reduction of device switching frequency, current and line voltage THD, thereby minimizing the filter size requirement of the inverter, employed in industrial applications, where sinusoidal output voltage is required.